Pengaruh Tingkat Pendidikan, Umur Usaha Dan Skala Usaha Pelaku UMKM Terhadap Penggunaan Informasi Akutansi - Eka Puspita Sari; Ida Ayu Nursanty; Rusli Amrul (Akuntabel: Jurnal Ilmiah Akuntansi, 2024)
Information so it can be decided thatthe level of education does not have a This study aims to determine the effect of the owner’s education level on the use of accounting informasion, to determine the effect of business age on the use of accounting information and to determine the effect of knowledge on the use of accounting information.the variables in this research are education level, business age and business scale.The population used in this research is all UMKM in batulayar district,west lombok.samles are taken using sampling. Data was obtained by distributing questionnaires to respondents in the UKM area in Batu layar sub-district.This research uses multiple linier analysis. The result of this research are thas business scale has a positive and significant of the use of accounting informaion.so it can be decided that business scale has a significant influence on the determinants of the use of accounting information among UMKM in batulayar subdistrict, Business age has no effect on the determinants of the use of accounting information. So it can be decided that the age of the business has no significant of the use of accounting information among UMKM in batulayar subdistrict and the level of education has a negative and significant effect on the determinants of the use of acounting significant influence on the determinants of the use of accounting information in UMKM in Batu layar.